STATUS KEBERLANJUTAN PENGELOLAAN HUTAN MANGROVE DI DESA SIDODADI KECAMATAN PADANG CERMIN KABUPATEN PESAWARAN PROVINSI LAMPUNG - Mukhlisi, Mukhlisi; Hendrarto, I.B.; Purnaweni, Hartuti (Jurnal Geografi, 2014)
This research was aimed to analyze sustainability of mangrove forestmanagement at Sidodadi village. Sustainability analysis was conducted by themethod of multidimensional scaling (MDS) approach with Rap-Simaforesttechniques (rapid appraisal index sustainable for the Sidodadi mangrove forest).The result of study showed that multidimensions management sustainability wasin moderate sustainable status or it sustainability index was 55,63%. Meanwhile,that ecological and economics dimension has low sustainable status. Both socialand legal-institutional dimensions have moderate sustainable status. The resultsof leverage analysis indicated that 15 out of 33 indicators were categorized assensitivity indicators affected sustainability of mangrove management at Sidodadivillage. These sensitive indicators should be involved in increasing sustainabilityindex in the future.